1994
DOI: 10.1038/ki.1994.195
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin is a mediator of anaphylactoid reactions during hemodialysis with AN69 membranes

Abstract: Anaphylactoid reactions (AR) are the most feared complications of hemodialysis. Recently, a high incidence of AR has been reported during dialysis with AN69 membranes in patients treated with ACE inhibitors. Plasma levels of C3a, histamine and bradykinin were measured in 12 patients at the onset of AR during dialysis with AN69. We also investigated bradykinin generation in 10 symptom-free patients dialyzed with four different membranes. None of the 12 patients studied during AR displayed excessive complement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 22 publications
4
67
0
Order By: Relevance
“…We report a high interindividual variation in the ability to generate bradykinin, which is in line with the experience from other clinical settings [23]. In addition, we also noted a high donation-to-donation variation within the same individual in a single experiment.…”
Section: Discussionsupporting
confidence: 70%
“…We report a high interindividual variation in the ability to generate bradykinin, which is in line with the experience from other clinical settings [23]. In addition, we also noted a high donation-to-donation variation within the same individual in a single experiment.…”
Section: Discussionsupporting
confidence: 70%
“…Patients experiencing hypersensitivity to dialysis membranes have been shown to have increased plasma levels of BK (Schaefer et al, 1993;Verresen et al, 1994). Lower serum aminopeptidase P activity differentiated dialysis patients who had experienced a hypersensitivity reaction to the negatively charged membrane from patients who had not experienced a reaction (Blais et al, 1999).…”
Section: B Renal Diseasementioning
confidence: 99%
“…To conclude: (a) Since in the early 1990s, a number of studies have concluded an increased frequency of anaphylactoid reactions in ACEI-treated hemodialyzed patients with AN-69 membrane [50, 51, 52, 53]; for these reactions the pathogenic agent was assumed to have increased the secretion of bradykinin (a tissue peptide hormone with a variety of direct or indirect – due to induction of the secondary mediators release – effects, which included vasodilation and bronchoconstriction) from the membrane by activation of Hageman factor [54, 55, 56, 57, 58]. (b) PAF synthesis and secretion are indeed induced by AN-69 membrane and as it is a very active vasodilator and bronchoconstrictor agent, it could also be implicated in the pathogenesis of acute anaphylactic type reaction of HD [7, 59].…”
Section: Discussionmentioning
confidence: 99%